Aedes aegypti (Diptera: Culicidae) Longevity and Differential Emergence of Dengue Fever in Two Cities in Sonora, Mexico. Issue 1 (2nd September 2016) - Ernst, Kacey C.; Walker, Kathleen R.; Reyes-Castro, Pablo; Joy, Teresa K.; Castro-Luque, A. Lucia; Diaz-Caravantes, Rolando E.; Gameros, Mercedes; Haenchen, Steven; Hayden, Mary H.; Monaghan, Andrew; Jeffrey-Guttierez, Eileen; Carrière, Yves; et al.
Abstract : Dengue virus, primarily transmitted by the Aedes aegypti (L.) mosquito, has rapidly expanded in geographic extent over the past several decades. In some areas, however, dengue fever has not emerged despite established Ae. aegypti populations. The reasons for this are unclear and have sometimes been attributed to socio-economic differences. In 2013 we compared Ae. aegypti adult density and population age structure between two cities in Sonora, Mexico: Hermosillo, which has regular seasonal dengue virus transmission, and Nogales, which has minimal transmission. Larval and pupal abundance was greater in Nogales, and adult density was only higher in Hermosillo during September. Population age structure, however, was consistently older in Hermosillo. This difference in longevity may have been one factor that limited dengue virus transmission in Nogales in 2013, as a smaller proportion of Ae. aegypti females survived past the extrinsic incubation period.